La expresión plástica y su incidencia en el desarrollo motriz de los niños de primer grado de educación básica de la escuela fiscal mixta “Pichincha” de la parroquia San Jacinto del Búa, cantón Santo Domingo, provincia Santo Domingo de los Tsáchila. Periòdo 2013-2014 - Zambrano Quiroz, Antonia Emelina (2015)
This thesis was aimed to investigate how "PLASTIC EXPRESSION AND ITS IMPACT ON DEVELOPMENT DRIVE IN CHILDREN OF FIRST STAGE OF BASIC EDUCATION SCHOOL MIXED FINANCIAL" Pichincha "PARISH SAN JACINTO BÙA, SANTO DOMINGO CANTON, PROVINCE SANTO SUNDAY TSÁCHILA. PERIOD 2013-2014 ".The same that has been developed according to the regulations of graduation at the National University of Loja and was generated according to the following problem: How does artistic expression in the development of children in basic first year? In this research the overall objective raised was: Contribute to the present research to improve the quality of education, teachers and parents know the importance of Plastic Expression as a theoretical and methodological tool for the Motor Development Children in first grade of elementary school. In the methodology, used methods were present: Scientific addressing the reality of the problem, Inductive to compare the information obtained in the fieldwork with the Theoretical Framework, Descriptive logical interpretation to facilitate through library research and results such as technical survey and the data collected was also used. With this research we noted the importance of artistic expression and influencing motor development of children first year of basic education. Because by conducting fieldwork they showed children with motor development and it was evident that the use of the techniques of artistic expression is important in early childhood education. Interpretation of the information presented in the tables pie charts, which allowed the checking targets showing the influence of the use of Plastic Expression Techniques in Early Childhood Education.